RELATIONSHIP BETWEEN THE CLASSICAL NUMERICAL RANGE AND ESSENTIAL NUMERICAL RANGES - Owego, D. O.; Okelo, N. B. (IJRDO -JOURNAL OF MATHEMATICS, 2015)
In this paper we discuss the relationships between the numerical range and the essentialnumerical range. We prove two theorems in this paper that show how the numerical rangeand the essential numerical range are related. Finally, we discuss the roles of the essentialnumerical range in operator theory.